STRENGTHENING REGIONAL REVENUE THROUGH GOVERNANCE AND STRATEGIC LOCAL SPENDING SYNERGY - Wardana, Muhammad Fadhil Kusuma; Firmansyah, Amrie (RISET: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2025)
This study investigates the effect of regional government expenditure and institutional quality on local own-source revenue in Indonesia during the COVID-19 pandemic. The analysis is based on data from 2021 to 2022 from 34 provincial governments in Indonesia, focusing on how local expenditure can influence local revenue. The study also examines the role of institutional quality in enhancing local revenue. The analysis method used in this study is regression using panel data with a random effect model (REM) as the best model. The results indicate that strategic regional expenditures such as tax incentives and social aid in times of crisis can significantly impact local revenue by stimulating local economic activities, keeping the purchasing power of society, and enhancing public services. Furthermore, the quality of government performance and good governance practices, such as the digitalization of services, positively influence local revenue by increasing public trust and improving administrative efficiency. The result demonstrates that strategic local expenditure, implemented with good governance, can boost taxpayer satisfaction, improve local revenue collection, and increase regional fiscal independence. This research provides valuable insights for policymakers, especially the Ministry of Finance and local governments, to optimize regional spending and governance in achieving regional independence.